Viewpoint: Practitioner and professor - Strengthening the relationship - William E. Sparkman (Educational Considerations, 1977)
A workshop provided an opportunity for mutual exploration of how the practitioner and the professor perceive each other in terms of roles, responsibilities, programs and constraints.